Hungarian Monitoring, 12 February 1990 . [Magyar rádiófigyelő], 1990. február 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Soviet supreme council presidium supports the creation of a presidential system in the USSR - German re-unification process - Voroncov on international Zionism - Open Skies conference in Ottawa Domestic Affairs: - Hungarian-Romanian Society formed in Budapest - Workers' Militia property - The Czinege case - Modified press law - Frequency moratorium - First decision by the Constitutional Court: the Parliament can modify the Constitution - Election: election programs, political announcements - On the demonstrations in Targu Mures Economy: - Common Market approves USD 1 billion loan for Hungary; interview with the Hungarian National Bank president - Soviet debt Külpolitika: - A SZU legfelsőbb tanácsának elnöksége állást foglalt az elnöki rendszer létrehozása mellett a SZU-ban - Német újraegyesítés folyamat - Voroncov a nemzetközi cionizmusról - Nyitott Égbolt tanácskozás Ottawában Belpolitika: - Magyar-Román Társaság alakult Budapesten - A Munkásőrség vagyona - Czinege ügy - A módosított sajtótörvény - Frekvencia moratórium - Alkotmánybíróság első határozata: az Országgyűlés módosíthatja az Alkotmányt - Választás: választási műsorok, politikai hirdetések - A marosvásárhelyi tüntetésről Gazdaság: - A Közös Piac jóváhagyta Magyarország számára az egymilliárd dolláros kölcsönt; interjú az MNB elnökével - A szovjet tartozás